The Enzymes: Energy coupling and molecular motors - Hackney, David D; Ed. Tamanoi, Fuyuhiko; Ed (Oxford : Elsevier Academic, 2004)
This volume examines a number of different molecular motors that utilize ATP. The molecular machines to be discussed include ATP synthase, myosin, kinesin, DNA helicases, DNA topoisomerases, chaperones and bacterial rotory motors. The discussion of these various molecular motors is rarely undertaken in one volume and will serve as a great resource for scientists studying structure and function of multiprotein complexes as well as those working on energy coupling mechanisms. The areas of research presented in this volume do not normally overlap, and yet they share common mechanisms. This volume examines a number of different molecular motors that utilize ATP. The molecular machines to be discussed include ATP synthase, myosin, kinesin, DNA helicases, DNA topoisomerases, chaperones and bacterial rotory motors. The discussion of these various molecular motors is rarely undertaken in one volume and will serve as a great resource for scientists studying structure and function of multiprotein complexes as well as those working on energy coupling mechanisms. The areas of research presented in this volume do not normally overlap, and yet they share common mechanisms.